Students’ Reflections on Teaching Methodology in Anatomy - Chopra, Jyoti; Rani, Anita; Rani, Archana; Deewan, RK; Srivastava, AK; Sharma, PK (Asian Journal of Medical Sciences, 2013)
Objective: With technological evolution, use of power point presentation has been increased tremendously for classroom teachings in medical education. There is dearth of information that whether this technology is really liked by the students in anatomy or not. Therefore present study was conducted to assess which methodology of teaching anatomy was preferred by students: traditional (chalk & black-board), computer assisted or both when combined. Methods: A questionnaire based study was conducted that involved 250 1st year MBBS students. Students were asked to fill semi structured questionnaire that contained closed and open ended questions regarding teaching methodology. Results & Conclusion: 70.37% students favored combination of power point presentations along with traditional method, 25.93% preferred chalk and blackboard method and only 3.7% students opined that power point presentations should be the sole method of teaching. Therefore the study concludes that traditional method of lecture delivery in anatomy should be carefully amalgamated with power point presentations to meet the aspirations of students and to combat the limitations of chalk and board method. DOI: http://dx.doi.org/10.3126/ajms.v5i1.8039 Asian Journal of Medical Science Vol.5(1) 2014 pp.47-51